2021
DOI: 10.26434/chemrxiv.14555841.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increasing the CO2 Reduction Activity of Cobalt Phthalocyanine by Modulating the σ-donor Strength of Axially Coordinating Ligands

Abstract: <p>Axial coordination of a pyridyl moieties to CoPc (either exogenous or within poly-4-vinylpyridine polymer) dramatically increases the complex’s activity for CO<sub>2</sub>RR. It has been hypothesized that axial coordination to the Co active site leads to an increase in the Co dz<sup>2</sup> orbital energy, which increases the complex’s nucleophilicity and facilitates CO<sub>2</sub> coordination compared to the parent CoPc complex. The magnitude of the energy increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Porphyrins and phthalocyanines have been studied as molecular electrocatalysts for the CO 2 RR, with cobalt phthalocyanine (CoPc) being a particularly well-studied catalyst due to its unique electron configuration and favorable binding energy to CO 2 . CoPc easily adsorbs to carbon electrode surfaces and has been an important model system to study the mechanism of the CO 2 RR , as well as one of the rare molecular catalysts able to reduce CO 2 to methanol under specific reaction conditions. , Our particular interest in CoPc has focused on improving the selectivity of CoPc-catalyzed CO 2 RR over the competing HER by encapsulating the parent complex within coordinating polymers to control the local microenvironment. Our group and others , have shown that encapsulating CoPc within poly­(4-vinylpyridine) (P4VP) results in increased reaction activity and selectivity for the CO 2 RR over the HER, leading to an increase in Faradaic efficiency for CO production from 60% for CoPc to >90% for CoPc-P4VP and a four-fold increase in turnover frequency for CO production. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Porphyrins and phthalocyanines have been studied as molecular electrocatalysts for the CO 2 RR, with cobalt phthalocyanine (CoPc) being a particularly well-studied catalyst due to its unique electron configuration and favorable binding energy to CO 2 . CoPc easily adsorbs to carbon electrode surfaces and has been an important model system to study the mechanism of the CO 2 RR , as well as one of the rare molecular catalysts able to reduce CO 2 to methanol under specific reaction conditions. , Our particular interest in CoPc has focused on improving the selectivity of CoPc-catalyzed CO 2 RR over the competing HER by encapsulating the parent complex within coordinating polymers to control the local microenvironment. Our group and others , have shown that encapsulating CoPc within poly­(4-vinylpyridine) (P4VP) results in increased reaction activity and selectivity for the CO 2 RR over the HER, leading to an increase in Faradaic efficiency for CO production from 60% for CoPc to >90% for CoPc-P4VP and a four-fold increase in turnover frequency for CO production. ,, …”
Section: Introductionmentioning
confidence: 99%